Psychology for cambridge international AS & A level coursebook - Russell, Julia (Newyork ; Cambridge University Press, 2022)
This coursebook is a valuable resource for students aiming to achieve a deep understanding of psychology and perform well in their examinations. Its structured approach, combined with interactive and supportive features, makes it an excellent choice for learners and educators alike.
A level
Keywords: Psychology